From Economic Abuse to Economic Empowerment: Piloting a Financial Literacy Curriculum With Women Who Have Experienced Domestic and Family Violence. Issue 4 (November 2019) - Warren, Amy; Marchant, Trudi; Schulze, Darcee; Chung, Donna
Economic abuse as a form of men's violence against women has only been recently recognized as a form of violence in its own right. It is known to further exacerbate the detrimental long-term impacts of domestic and family violence on women and children. There is evidence to suggest the effectiveness of financial literacy programs in mitigating some of these impacts and improving women's financial well-being in the longer term; however, there are very few domestic violence–informed, empirically evaluated programs internationally. This article reports the findings of a specialist domestic violence financial literacy curriculum, which was developed and piloted in Western Australia using pre–post measures and focus groups. These findings suggest that such financial literacy programs delivered in refuge settings have effective short-term outcomes among women. Lessons learned from the pilot and the implications for future implementation and scaling up of programs and research are also discussed.